Novel Research in Sexuality and Mental Health - Montejo, Angel L. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Sexuality is considered as a great human value related to happiness and satisfaction, but unfortunately, when affecting mental disorders, they tend to be associated with second level human functions. Nevertheless, sexual dysfunction often accompanies psychiatric disorder, intensely influencing compliance, quality of life and human relationships. Sexuality could be influenced either by a mental disorder itself, difficulties to get and maintain couple relationships or by the use of psychotropic treatments. Treatment-related adverse events are unfortunately under-recognized by clinicians, scarcely spontaneously communicated by patients, and rarely investigated in clinical trials. The most frequent psychotropic compounds that could deteriorate sexuality and quality of life include antidepressants, antipsychotics and mood regulators. There are important differences between them related to some variations in mechanisms of action including serotonin, dopamine and prolactin levels. Little is known about the relevance of sexuality and its dysfunctions in chronic and frequent mental and neurological disorders, such as psychosis, mood disorders, anxiety, phobias, eating disorders, alcohol or drug dependencies, epilepsy and childhood pathology. Poor sexual life, low satisfaction and more frequent risky sex behavior than in the general population are associated with severe mental diseases. There is a need for increasing research in this field, including epidemiological, psychological, neurophysiological, neuroanatomical and genetic variables related to sexual life to get a better understanding of the implicated mechanisms. To increase the sensibility of clinicians, the identification and management of sexual disturbances after the onset of any mental disorder should be highlighted. This would avoid unnecessary suffering and deterioration of quality of life.